Gram-Negative Infections in Adult Intensive Care Units of Latin America and the Caribbean. (27th November 2014) - Luna, Carlos M.; Rodriguez-Noriega, Eduardo; Bavestrello, Luis; Guzmán-Blanco, Manuel
Abstract : This review summarizes recent epidemiology of Gram-negative infections in selected countries from Latin American and Caribbean adult intensive care units (ICUs). A systematic search of the biomedical literature (PubMed) was performed to identify articles published over the last decade. Where appropriate, data also were collected from the reference list of published articles, health departments of specific countries, and registries. Independent cohort data from all countries (Argentina, Brazil, Chile, Colombia, Cuba, Mexico, Trinidad and Tobago, and Venezuela) signified a high rate of ICU infections (prevalence: Argentina, 24%; Brazil, 57%). Gram-negative pathogens, predominantly Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli, accounted for > 50% of ICU infections, which were often complicated by the presence of multidrug-resistant strains and clonal outbreaks. Empirical use of antimicrobial agents was identified as a strong risk factor for resistance development and excessive mortality. Infection control strategies utilizing hygiene measures and antimicrobial stewardship programs reduced the rate of device-associated infections. To mitigate the poor health outcomes associated with infections by multidrug-resistant Gram-negative bacteria, urgent focus must be placed on infection control strategies and local surveillance programs.